Corporate intelligence: modern view and development trends - I. P. Akimova; O. A. Dmitrieva; A. V. Vlasov (Путеводитель предпринимателя)
Corporate intelligence — this term has only recently appeared in our country, but it is already widely used in business. And even managed to acquire stereotypes: some consider corporate intelligence analogous to industrial espionage, others imagine it as a game of office workers in « James Bond», and the rest do not understand why it is needed in the enterprise.Corporate intelligence specialists analyze available information and check all market sources in order to make an assessment of all possible threats and risks to the business.